Kandungan Bahan Aktif Tumbuhan Serai (Cymbopogon citratus) dan Pemanfaatannya dalam Bidang Kesehatan - Nadyanka Zafirah Daya Adiwiguna; Hendra Tarigan Sibero; Arif Yudho Prabowo; Khairun Nisa Berawi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The use of herbal plants such as Cymbopogon citratus (lemongrass) is increasingly important in the development of safe and sustainable natural therapies. This plant is widely used in Southeast Asia, including Indonesia, as a culinary ingredient and in traditional medicine. This study aims to identify the main bioactive compounds and the use of C. citratus in the health sector. The method used was a data-based literature review from Scopus from 2020 to 2025 with a PICOS approach to synthesize experimental, clinical, and systematic studies. The results show that lemongrass contains major compounds such as citral, geraniol, limonene, apigenin, and other flavonoids that have antibacterial, antifungal, anticancer, anti-inflammatory activities, as well as the ability to regulate glucose metabolism, cholesterol, and liver function. Several clinical trials have demonstrated the benefits of lemongrass aromatherapy in reducing anxiety and blood pressure. Overall, these findings reinforce the evidence that C. citratus has potential as a multifunctional therapeutic agent and a base material for phytopharmaceutical development.